ANALISIS AKAD ULANG PRODUK PEMBIAYAAN MURABAHAH BAITUL MAAL WAT TAMWIL MITRAMU CABANG PASAR RATU JEPARA MENURUT FATWA DSN-MUI NOMOR 48/DSN-MUI/II/2005 - Laila, Mega Nor; Mubarok, Ahmad Fauzan (Institut Agama Islam Syubbanul Wathon Magelang, 2025)
This study analyzes the implementation of contract restructuring (akad ulang) for Murabahah financing products at BMT Mitramu, Pasar Ratu Jepara Branch, based on the provisions of DSN-MUI Fatwa No. 48/DSN-MUI/II/2005 concerning the re-determination of the selling price in Murabahah contracts. Employing a descriptive qualitative approach, this research utilizes data triangulation through in-depth interviews, observations, and document analysis. The findings indicate that the contract restructuring process involves three main stages: preventive communication, deliberation and adjustment of the financing scheme, and formal re-contracting. The process is based on mutual agreement without increasing the principal debt or profit margin and only charges a real administrative fee. The new contract is legally formal and independently binding. This practice demonstrates compliance with sharia principles and institutional ethics, showing that contract restructuring serves as a legitimate, responsive, and fair contractual reconstruction within the framework of Islamic economic law.